Impact of Disaster on Underprivileged Children in Covid-19 Pandemic: Policy Response for Emergency Education - Mukherjee, Mrinal; Maity, Chanchal; Chatterjee, Somdutta (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
It is necessary to recognize and address the differential impact of disasters on society. It is quite possible that a significant number of children to become victims of the COVID-19 caused social disaster. As a result, there would be an increase in the number of school dropouts and child labor, which indicates a substantial number of children will be deprived of their right to education. Any alternative response during school closure, like internet-based remote teaching learning, might not compensate the loss of learning as nearly half of the world is without access to the internet. "Emergency situations" are considered any situation either man-made or natural disasters suddenly disrupt the normal course of life, empathy and educational opportunities of children. The present study intended to find out the nature of social disaster caused by COVID-19 and how it impacted the learning loss and socio-emotional immunity of the under privileged school going children. A narrative review technique was used for this research study to explore the policy advocacies adopted in emergency basis in mitigating the impacts of the ongoing pandemic on such underprivileged children. The data were derived from published articles and reports available in national and international data repositories. The findings reveal that the closure of schools raise the vulnerability of underprivileged children as they are being deprived of their right to education and socio-emotional security. Present pandemic has led adverse situation, therefore disrupted delay or deny the right to education. It is time to rethink to adopt a new policy and mechanism to continue their education and to provide socio-emotional immunity in the time of emergency to address the gravity of crisis.